Hubungan Relasional Strategi Resource-Based View dan Entrepreneurial Skill terhadap Inovasi dan Keunggulan Kompetitif Lembaga Bimbingan Belajar di Wilayah Malang - Winoto, Agung Budi; Hadiwidjojo, Djumilah (Jurnal Aplikasi Manajemen, 2015)
This research aims to determine the relationship of resource-based view strategyand entrepreneurial skills to the innovation ability and competitive advantage on courseinstitutes in Malang. This research uses 134 samples by around 202 total population ofcourse institutes in Malang. The study was conducted by selecting a course institute that hasbeen operated their organizations at least three (3) years ago, and selecting respondentswho served as an active manager in each course institute. The instrument analysis of theresearch is primary data through interviews using questionnaires, and observation for otherssupporting data as the secondary data. The results of the research shows that the resource-based view strategy have a positive effect on innovation ability and competitiveadvantage on course institutes in Malang. Meanwhile, entrepreneurial skills are also havepositive and significant effect to innovation ability and competitive advantage on theseinstitutes. By the research, known that innovation variables have the significant affect forcompetitive advantage variables on course institutes in Malang. This research is highlyrecommended for course institutes in Malang in order to expand their business scope. Therelationship of resource-based view strategy and entrepreneurial skills for innovation abilityand competitive advantage on course institutes in Malang requires continuous improvementto develop the quality of non-formal education in the future.